A New Reduced Voltage Stress ZVT-ZVS PWM Full-Bridge DC-DC Converter - Sahin, Yakup; Aksoy, Ismail; Ting, N. Suleyman (IEEE, 2015)
A new reduced voltage stress soft switching PWM current fed Full-Bridge DC-DC converter for fuel cells and photovoltaic cells applications is proposed in this study. The snubber cell provides Zero Voltage Transition (ZVT) turn on and Zero Voltage Switching (ZVS) turn off together for main switches in the converter. The voltage stresses of the main the switches are reduced and turning them off became better by adding an extra passive component. Besides, all components operate under soft switching, the current or voltage stresses on the auxiliary component are quite in acceptable level, and the main devices do not have any additional current stresses. In addition, the simplified structure makes the novel converter easy to control. Detailed analysis and synthesis of the new converter is introduced, and usefulness of the design is confirmed by simulation studies of a 1.5 kW and 25 kHz full bridge converter.
Keywords: Soft switching; active snubber cells; zero voltage transition; zero voltage switching; Energy & Fuels; Engineering